Análise energética dos processos do aterro sanitário metropolitano de João Pessoa/PB - Nascimento, Dayse Pereira do (2020)
The current society is looking for ways to reach a sustainable society, in which economic growth is combined with environmental conservation. One of the biggest problems faced by Brazilian municipalities is to adopt policies for the adequate management of Urban Solid Waste (USW) in order to avoid the proliferation of diseases and environmental contamination. The National Policy on Solid Waste (Law No. 12.305/2010) in Brazil determines that USW should be sent to the landfill, and possible sources of energy. The city of João Pessoa / PB destines its USW to the Metropolitan Sanitary Landfill of João Pessoa (ASMJP), where the biogas collected in the landfill is currently being burned (no use). The objective of this work is to verify the technical and economic viability of the implementation of a biogas capture system for electric power generation in ASMJP. For this, the USW data deposited in the ASMJP were collected, in order to apply methods that quantify the biogas generation in the landfill. Three methods were applied: USEPA, IPCC and GasSim; the GasSim method developed by the UK environmental agency was the most refined method and therefore was chosen for the estimation of biogas production. Three scenarios for biogas generation in the ASMJP (more likely, optimistic and pessimistic) were formulated for future sensitivity analyzes. It was observed that the ASMJP has a considerable biogas generation, generating 11277,28 t/year in its peak production that occurs in the year of its activities (2028). The biogas generation potential can be optimized if a better separation of the USW deposited in the ASMJP (increasing the proportion of organic matter) and still increase the life of the landfill occurs. Jenbacher and Caterpillar engines were selected for further analysis because of the availability of manufacturer's manuals online. After setting the engine production and operating restrictions, the Jenbacher 620 GS-BL (F21) engine was selected due to higher electricity production, which could reach 21313080,00 kWh over its life cycle. With the choice of the engine was designed a cogeneration plant, which from 2019 the value of cats reduces significantly due to the equipment amortization. After 16 years of operation, the cogeneration plant starts to make a profit, at the end of the life of the landfill the total sum of annual net results is a little over R$ 29 million positive.